Effect of hydroxyurea on quality of life with a moderating role of healthcare professionals’ performance: A view from the beta-thalassemia patients. - Sheikh , Affaf; Bibi , Munaza; Siddiqui , Saima; Perveen , Kousar; Shamsi , Tahir (International Journal of Endorsing Health Science Research, 2022)
Background: Transfusion-dependent (TDT) β –Thalassemia patients have lower HRQoL than healthy individuals. The impact of Hydroxyurea is always measured with the clinical investigations in terms of laboratory diagnosis. This study aimed to seek out the impact of the drug Hydroxyurea on improving physical health problems of Quality of Life (QoL) of β – Thalassemia patients with the moderating role of healthcare professionals. Methodology: In this research, a deductive approach was adopted whereby hypotheses were originated first, followed by organizing a well-structured questionnaire as a tool for measuring the data. The nature of the research was explanatory and based on primary quantitative data. The data was collected from 290 patients visited in the outpatient and daycare departments of the National Institute of Blood Diseases and Bone Marrow Transplantation Hospital. Results: This study revealed that the impact of Hydroxyurea therapy on improving the physical health problems of Beta Thalassemia is not evident as per the analysis (r=0.079; p=0.178). Similarly, a weak positive non-significant correlation exists between Hydroxyurea therapy and the performance of healthcare professionals in the hospital (r=0.016; p=0.782). Moreover, no significant improvement was observed in physical health problems and health domain of QoL of BT patients by moderating the role of healthcare professional performance (p=0.4471 and 0.4102, respectively). Conclusion: It is concluded that moderating the role of healthcare professionals' performance does not improve the impact of Hydroxyurea on physical health problems and domains of QoL of β – Thalassemia patients.